THE ROLE OF INTERACTIVE METHODS IN IMPROVING THE EFFECTIVENESS OF EDUCATION IN SECONDARY SCHOOLS (Scientific journal of the Fergana State University, 2026)
This article presents information about methods to improve the effectiveness of education in secondary schools. It demonstrates, based on experiments, that by applying modern technologies such as STEM and SMART methods, students’ knowledge increased by 20–30 percent.